2016
DOI: 10.1177/1742271x16674039
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between ultrasound scanning ability (sonography) and visuospatial perception or psychomotor ability?

Abstract: Background: Competent sonography is thought to include a unique combination of skills not yet fully defined. This presents challenges when recruiting the correct people for training. Skills are thought to include visuospatial perception and psychomotor skills, but little is known about the relationship between these aptitudes and scanning ability. This feasibility study explored such relationships, to identify evaluation techniques which may improve selection and recruitment. Methods: A sample of 30 experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A challenge is the level of educational investment that is required for the training of sonologist-clinicians. Users of CPUS must master a range of skills that include cognitive mastery of ultrasound theory, technical mastery of the ultrasound machine, anatomical knowledge, ability to conceptualize anatomy in “3-D”, psychomotor skills to manipulate an ultrasound probe with one hand while operating a machine with the other, and the ability to integrate the information obtained by ultrasound into clinical practice [ 36 , 37 ]. The “muscle memory” to simultaneously operate the ultrasound machine with one hand and the transducer with the other requires extensive repetition.…”
Section: Discussionmentioning
confidence: 99%
“…A challenge is the level of educational investment that is required for the training of sonologist-clinicians. Users of CPUS must master a range of skills that include cognitive mastery of ultrasound theory, technical mastery of the ultrasound machine, anatomical knowledge, ability to conceptualize anatomy in “3-D”, psychomotor skills to manipulate an ultrasound probe with one hand while operating a machine with the other, and the ability to integrate the information obtained by ultrasound into clinical practice [ 36 , 37 ]. The “muscle memory” to simultaneously operate the ultrasound machine with one hand and the transducer with the other requires extensive repetition.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported a significant relationship between the Dimensionless Squared Jerk, a validated motion metric that measures deliberate hand movements, and US expertise in obstetric US [ 58 ], while the other three papers did not find a significant relationship between psychomotor skills and US competence. [ 45 , 48 , 49 ] No correlation or determination coefficient was reported in the studies. Walker [ 49 ] found a regression coefficient of 0.00056 ( p = 0.580) for the Grooved Pegboard test performed by the non-dominant hand, and of − 0.0013 ( p = 0.329) when it was executed by the dominant hand, and time to complete an ultrasound guided cystocentesis task.…”
Section: Resultsmentioning
confidence: 99%